Using Critical Care Simulations to Prepare Nursing Students for Capstone Clinical Experiences. Issue 2 (March 2018) - Smallheer, Benjamin; Hunt, Jennifer; Smith, Judson
Abstract : The purpose of this innovative learning strategy was to decrease students' fear and anxiety within the critical care environment before the initiation of a critical care capstone clinical experience by enhancing their familiarity of the critical care environment through deliberate practice and experiential learning. This will in turn increase student knowledge and competence in the critical care setting. Critical care units are often used during a capstone clinical experience to enhance critical thinking and clinical reasoning. Student preparation for these rotations, however, is varied and often inadequate. The resulting fear and anxiety impair learning and also contribute to an unsafe environment for this at-risk population. Before the capstone experience, students participated in 3 simulation experiences, each addressing a core concept of critical care nursing. Faculty engaged students during the simulations, while modeling the confidence and critical thinking of a critical care nurse. After both the critical care simulation and the capstone rotation, students stated that the simulation allowed them the time in a safe environment to critically think through the steps to care for critical patients before the capstone rotation. The experience provided them with increased confidence necessary to discharge the responsibilities of a critical care nurse—attention to critical thinking and reasoning. Mindfully constructed simulations with clear objectives help to inoculate the student against fears associated with high-risk patients. This decrease in fear and anxiety before a hands-on clinical experience may improve patient safety. More confident students are also better able to engage in both experiential and deliberate learning, resulting in a more enhanced and meaningful clinical experience.